Genomic and Transcriptomic Resources for Marker Development in Synchytrium endobioticum , an Elusive but Severe Potato Pathogen - Busse, Friederike; Bartkiewicz, Annette; Terefe-Ayana, Diro; Niepold, Frank; Schleusner, Yvonne; Flath, Kerstin; Sommerfeldt-Impe, Nicole; Lübeck, Jens; Strahwald, Josef; Tacke, Eckhard; Hofferbert, Hans-Reinhard; Linde, Marcus; et al. (Phytopathology, 2017)
Synchytrium endobioticum is an obligate biotrophic fungus that causes wart diseases in potato. Like other species of the class Chytridiomycetes, it does not form mycelia and its zoospores are small, approximately 3 μm in diameter, which complicates the detection of early stages of infection. Furthermore, potato wart disease is difficult to control because belowground organs are infected and resting spores of the fungus are extremely durable. Thus, S. endobioticum is classified as a quarantine organism. More than 40 S. endobioticum pathotypes have been reported, of which pathotypes 1(D1), 2(G1), 6(O1), 8(F1), and 18(T1) are the most important in Germany. No molecular methods for the differentiation of pathotypes are available to date. In this work, we sequenced both genomic DNA and cDNA of the German pathotype 18(T1) from infected potato tissue and generated 5,422 expressed sequence tags (EST) and 423 genomic contigs. Comparative sequencing of 33 genes, single-stranded confirmation polymorphism (SSCP) analysis with polymerase chain reaction fragments of 27 additional genes, as well as the analysis of 41 simple sequence repeat (SSR) loci revealed extremely low levels of variation among five German pathotypes. From these markers, one sequence-characterized amplified region marker and five SSR markers revealed polymorphisms among the German pathotypes and an extended set of 11 additional European isolates. Pathotypes 8(F1) and 18(T1) displayed discrete polymorphisms which allow their differentiation from other pathotypes. Overall, using the information of the six markers, the 16 isolates could be differentiated into three distinct genotype groups. In addition to the presented markers, the new collection of EST from genus Synchytrium might serve in the future for molecular taxonomic studies as well as for analyses of the host–pathogen interactions in this difficult pathosystem. [Formula: see text] Copyright © 2017 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .